Effects of Phosphate-Solubilizing Bacteria and Organic Fertilizer Types on the Vegetative Growth of Waxy Maize (Zea mays var. ceratina) - Dina Nurdiana Dai; Hayatiningsih Gubali; Zulzain Ilahude (International journal of technology and education research, 2026)
Abstract Phosphorus (P) availability in soil is frequently a limiting factor for waxy maize growth due to high phosphorus fixation capacity, particularly in acidic soils. The application of phosphate-solubilizing bacteria (PSB) and organic fertilizers represents an environmentally sound approach to enhancing P bioavailability and overall soil fertility. This study evaluated the effects of PSB and different types of organic fertilizer on the vegetative growth of waxy maize, as well as their interaction. The study employed a 4 × 3 factorial Randomized Block Design (RBD) with three replications. The first factor was PSB dose, consisting of four levels: 0, 10, 20, and 30 mL ha⁻¹, and the second factor was organic fertilizer type, consisting of three levels: no fertilizer, 15 t ha⁻¹ of cattle manure, and 15 t ha⁻¹ of chicken manure. The observed parameters included plant height, number of leaves, and leaf area. The data were analyzed using ANOVA and the 5% DMRT test. The results showed that the application of Phosphate-solubilizing bacteria (PSB) had no significant effect on all vegetative growth parameters. Conversely, the type of organic fertilizer had a significant effect, with chicken manure yielding the best growth in terms of plant height, number of leaves, and leaf area. There was no significant interaction between the phosphate-solubilizing bacteria dose and the type of organic fertilizer. Keywords: waxy maize, phosphate-solubilizing bacteria, organic fertilizer, vegetative growth